Sistem Monitoring Kualitas Air Tambak Budidaya Udang Litopanaeus vannamei Menggunakan NodeMCU ESP32 Berbasis IoT - Eza Ariyani; Sri Wahyu Suciyati; Donni Kis Apriyanto; Amir Supriyanto (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
Abstract. In this research a water quality monitoring system was designed that is capable of monitoring temperature, pH, and Total Dissolve Solid (TDS) using an Internet of Things (IoT)-based NodeMCU ESP32 in the water quality of Litopenaeaus vannamei shrimp ponds. In this study, E201-C BNC Kit version pH sensor, DFRobot TDS sensor and DS18B20 waterproof sensor controlled by ESP32 microcontroller were used. The working principle of this system is that when the sensor is inserted into the shrimp pond, the sensor will detect the water quality. The measurement result will be processed by ESP32 and displayed on LCD and telegram. The telegram application can receive data when measuring using the long poll method. The sensor test mechanism is carried out by comparing the sensor reading with a calibrated device. E201-C BNC version Kit pH sensor tests were conducted using an acid (vinegar) solution, a DFRobot TDS sensor with a TDS-3 meter, and a DS18B20 waterproof sensor using an HTC-2 thermometer. The results of the study show that the sensor can detect pH, TDS, and temperature values ​​with an accuracy of 98.87%, 98.33% and 98.73% for each parameter. Keywords: ESP32, water quality, monitoring system, shrimp pond, telegram.